2017
DOI: 10.1371/journal.pone.0187870
|View full text |Cite
|
Sign up to set email alerts
|

Developing methods for assessing abundance and distribution of European oysters (Ostrea edulis) using towed video

Abstract: Due to large-scale habitat losses and increasing pressures, benthic habitats in general, and perhaps oyster beds in particular, are commonly in decline and severely threatened on regional and global scales. Appropriate and cost-efficient methods for mapping and monitoring of the distribution, abundance and quality of remaining oyster populations are fundamental for sustainable management and conservation of these habitats and their associated values. Towed video has emerged as a promising method for surveying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Other options include acoustic methods, foreshore sampling at low tide and diving campaigns, but the former is unsuitable for many of the metrics that restoration projects need to monitor (such as oyster size and density), while the latter is restricted by both depth and conditions at sea, which limits its utility in many situations. It is therefore critical that novel submarine technologies and monitoring methods are explored; indeed some are already in the process of development (Thorngren, Dunér Holthuis, Lindegarth, & Lindegarth, 2017). A further monitoring challenge is presented by the low concentration of the larvae of this species which makes it difficult to identify its presence in the water column.…”
Section: Resultsmentioning
confidence: 99%
“…Other options include acoustic methods, foreshore sampling at low tide and diving campaigns, but the former is unsuitable for many of the metrics that restoration projects need to monitor (such as oyster size and density), while the latter is restricted by both depth and conditions at sea, which limits its utility in many situations. It is therefore critical that novel submarine technologies and monitoring methods are explored; indeed some are already in the process of development (Thorngren, Dunér Holthuis, Lindegarth, & Lindegarth, 2017). A further monitoring challenge is presented by the low concentration of the larvae of this species which makes it difficult to identify its presence in the water column.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings of this study, high‐density areas or beds could, however, be selected and studied in more detail (i.e., demographic structure and spatfall), using, for example, scuba diving. Furthermore, previous evaluations of the method have shown that burial and coverage under other oysters or vegetation may lead to underestimation of abundance by on average 20% (Thorngren et al, ). Using common practice for corrections of sampling efficiency (Powell, Ashton‐Alcox, & Kraeuter, ; Tully & Clarke, ) that would mean the estimated size of the Swedish O. edulis population may be raised by a factor of 1.25–45.7 million adult oysters.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of oysters was carried out using a method developed and evaluated during spring 2013, described in (Thorngren, Holthuis, Lindegarth, & Lindegarth, ), with the difference that a flat‐bottomed boat with a step‐less electric engine was used to maneuver the sled. Once in position at a sampling site, a random number table (with the accuracy of 0.1 m) was used to determine the specific sampling depth within the strata.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations